Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Answer:
[tex]{ \tt{ {2x}^{2} - {3y}^{2} + 2k - 6y + 2 = 0 }} \\ { \tt{ \{x = 3 \: \: and \: \: y = - 2 \}}} \\ { \tt{ {2(3)}^{2} - {3( - 2)}^{2} + 2k - 6( - 2) + 2 = 0}} \\ { \tt{18 - 12 + 2k + 12 + 2 = 0}} \\ { \tt{2k + 20 = 0}} \\ { \tt{2k = - 20}} \\ { \tt{k = - 10}}[/tex]
Answer:
⇒ k=−9
Step-by-step explanation:
then put P(−2, 2) and we get,
x
2
−7x+ky=0
(−2)
2
−7(−2)+k(2)=0
⇒ 4+14+2k=0
⇒ 18+2k=0
⇒ 2k=−18
⇒ k=−9
again point Q(3, a) lies on the locus
the, put Q(3, a) and k=−9. We get
x
2
−7x+ky=0
(3)
2
−7(3)+(−9)×a=0
9−21−9a=0
−9a=+12
a=
9
−12
a=
3
−4
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.